2021
DOI: 10.3390/cells10112890
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Schizophrenia: Current Literature and Future Perspective

Abstract: Schizophrenia is a neuropsychiatric disorder characterized by dissociation of thoughts, idea, identity, and emotions. It has no central pathophysiological mechanism and precise diagnostic markers. Despite its high heritability, there are also environmental factors implicated in the development of schizophrenia. Epigenetic factors are thought to mediate the effects of environmental factors in the development of the disorder. Epigenetic modifications like DNA methylation are a risk factor for schizophrenia. Targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 226 publications
(310 reference statements)
0
26
0
Order By: Relevance
“…In particular, the abnormal behavioral phenotypes of the MAM model are developed through extended trajectories consistent with the natural history of schizophrenia, with alterations related to positive symptoms that tend to manifest later compared to social withdrawal and cognitive deficits ( Gomes et al, 2016 ). In addition, in utero MAM exposure is known to induce widespread, long-lasting DNA ( Perez et al, 2016 ) and histone hypermethylation ( Maćkowiak et al, 2014 ), which are factors supported by recent epigenetics research to be potential molecular links between genetic and environmental risk factors ( Magwai et al, 2021 ). This gives the MAM model additional construct validity and valuable research potential, such as to identify hypermethylated genes that contribute to distinct behavioral or circuit alterations [example studies, see: Gulchina et al (2017) ].…”
Section: Importance Of Reverse Translation Approach In Animal Models:...mentioning
confidence: 99%
“…In particular, the abnormal behavioral phenotypes of the MAM model are developed through extended trajectories consistent with the natural history of schizophrenia, with alterations related to positive symptoms that tend to manifest later compared to social withdrawal and cognitive deficits ( Gomes et al, 2016 ). In addition, in utero MAM exposure is known to induce widespread, long-lasting DNA ( Perez et al, 2016 ) and histone hypermethylation ( Maćkowiak et al, 2014 ), which are factors supported by recent epigenetics research to be potential molecular links between genetic and environmental risk factors ( Magwai et al, 2021 ). This gives the MAM model additional construct validity and valuable research potential, such as to identify hypermethylated genes that contribute to distinct behavioral or circuit alterations [example studies, see: Gulchina et al (2017) ].…”
Section: Importance Of Reverse Translation Approach In Animal Models:...mentioning
confidence: 99%
“…Another unsolved issue is that less is known about whether the variance of subcortical morphological connectivity is driven by gene expression patterns and epigenetic mechanisms, which are the plausible molecular basis of phenotypic heterogeneity across individuals with schizophrenia. Epigenetic modifications are proposed to mediate between environmental insults and gene expression and alter and stably maintain the expression of genes ( Magwai et al, 2021 ). DNA methylation (DNAm) is the most widely explored epigenetic mechanism and has been suggested to be associated with an antipsychotic drug action mechanism ( Ovenden et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is a heritable epigenetic modification which alters gene expression[ 4 ]. Studies have demonstrated that overall DNA hypomethylation is evident in SCZ patients, while treatment with haloperidol might increase methylation[ 5 , 6 ]. In other words, DNA methylation, which can regulate gene expression, is closely associated with the risk of SCZ [ 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%